Mutual impedance of circular plate for axially symmetric free vibrations at high frequency of radiating waves - W. RDZANEK (Archives of Acoustics, 2014)
Mutual normalized impedance of radiation of single axially symmetric normal modes is analysed for a circular clamped plate with a plane rigid baffle. Damping in the plate is ignored and the acoustic waves are assumed to radiate in a homogeneous lossless fluid medium. Selecting an integral representation of the considered acoustic impedance and using the Cauchy theorem of residues, an expression is obtained in an elementary form valid for high frequencies.